2012
DOI: 10.1162/jinh_a_00304
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Reproductive Behavior during the Demographic Transition

Abstract: New evidence from the Utah Population Database (UPDB) reveals that at the onset of the fertility transition, reproductive behavior was transmitted across generations--between women and their mothers, as well as between women and their husbands' family of origin. Age at marriage, age at last birth, and the number of children ever born are positively correlated in the data, most strongly among first-born daughters and among cohorts born later in the fertility transition. Intergenerational ties, including the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 19 publications
7
38
1
Order By: Relevance
“…Responses were coded, in agreement to the previous literature (Axinn et al 1994; Coombs 1974; Jennings et al 2012), into a scale with values ranging from 1 to 19, with a higher value indicating a preference for more children. For example, a respondent who says she prefers three children in the first question, and three is the maximum number of children she would prefer, receives a code of 7, as compared to a code of 10 for a respondent who says that three is the minimum number of children she would prefer.…”
Section: Methodsmentioning
confidence: 99%
“…Responses were coded, in agreement to the previous literature (Axinn et al 1994; Coombs 1974; Jennings et al 2012), into a scale with values ranging from 1 to 19, with a higher value indicating a preference for more children. For example, a respondent who says she prefers three children in the first question, and three is the maximum number of children she would prefer, receives a code of 7, as compared to a code of 10 for a respondent who says that three is the minimum number of children she would prefer.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study based on the Utah Historical Database, however, found higher fertility among women with living mothers and mothers-in-law during the fertility transition (Jennings et al 2012). The finding is consistent with research in evolutionary anthropology that stresses the importance of economic and physical assistance from relatives, particularly post-menopausal grandmothers, in the rearing of human children.…”
Section: Prior Research On the Us Fertility Transitionmentioning
confidence: 99%
“…The timing of births is an aspect of fertility behavior that has been found to have an intergenerational component (Jennings et al, 2012; Reher et al, 2008). Cox proportional hazard models are fit for age at first birth for index individuals (Cox, 1972).…”
Section: Methodsmentioning
confidence: 99%
“…Feelings of closeness with family are also associated with stronger intergenerational fertility correlations (McAllister et al, 1974). Adult women with a living mother are at higher risk of progressing to another birth than are women whose mothers are deceased, suggesting that mothers have an effect on the fertility of their daughters that extends beyond socialization and the environment of the childhood home (Jennings, Sullivan, & Hacker, 2012). Evolutionary studies of human behavior have also demonstrated the importance of kin on fertility.…”
Section: Introductionmentioning
confidence: 99%